Pengaruh Modal Usaha dan Motivasi terhadap Minat Berwirausaha Pada Mahasiswa Tingkat Akhir Ekonomi Syariah Universitas Ibn Khaldun Bogor - Said, Alfian (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Bogor This research method uses quantitative methods, taking data directly from the object of research in the form of disseminating questioners directly to final year students of Islamic economics, Ibn Khaldun University, Bogor. By presenting facts or realities that occur in the field that are observed through observation, field notes and distribution of questionnaires to final year students of Islamic Economics Ibn Khaldun University Bogor. This study aims at 1). Knowing the influence of business capital and motivation on entrepreneurship in final year students majoring in Islamic Economics at Ibn Khaldun University Bogor. 2). Knowing how to motivate entrepreneurial interest in final year students majoring in Sharia Economics, Ibn Khaldun University, Bogor.The results of research in this thesis that the influence of business capital and motivation in entrepreneurial interest in final year students of Sharia Economics at Ibn Khaldun University Bogor. Included in the positive category between independent variables, namely business capital and motivation, and dependent variables, namely entrepreneurial interest. It can be proven by the following results: 1) the results of the t test above obtained the calculated value of the Business Capital variable (X1) of 14.106 with a significance value of 0.000 < 0.05, the Motivation variable (X2) of 2.061 with a significance value of 0.000 < 0.05 So it can be concluded that the Motivation variable (X2) partially has a significant influence on Entrepreneurial Interest (Y). So that the presentation results of the data efficiency obtained in this study amounted to 78.1%.